Motives and constraints to bike tourism in Greece: “the Go-bike” project - Ntovoli, Apostolia; Karagiorgos, Thomas; Myrovali, Glykeria; Anoyrkati, Eleni; Papadopoulou, Sousana; Tamiakis, Iason; Alexandris, Kostas (Frontiers in Sports and Active Living, 2024)
Introduction: Bike tourism is one of the fast-developing alternative forms of tourism since it can satisfy the main pillars of sustainability (economic, social, and environmental). The current study is part of a larger funded project (GoBike) and aims to profile bike tourists in Greece, examine the motives and constraints to tourism participation, and show the value of using technology as a means of promoting bike tourism Methods: The data was collected through a quantitative study, with one hundred and five individuals who had experience with bike tourism activities, with the use of an online questionnaire. Items were used to measure socio-demographics, motives, constraints, involvement, and attitudes toward a smartphone application.The results indicated that «Nature», «Health», «Bike eco-friendly place» and «Interesting places» were the most important motives. On the other hand, the lack of «Guides», «Appropriate Routes» «Bike tourism Programs» and «Limited Information» were reported as the most important barriers. The bikers reported that technology can facilitate their decision to do bike tourism activities.Discussion: A smartphone application should include several attributes the most important of which are the «Elevation difference», the «warnings of obstacles/risks», «the level of difficulty», «the bike distance» and the «condition of the routes».